(untitled) (Research, Society and Development, 2020)
The contamination of waterbodies is a worldwide concern due to the increasing urbanization and industrialization of the cities without good effluent management. Touristic cities can suffer with the number of people during high seasons periods, which can lead to an elevated use of natural resources and effluents discharges. Moreover, raining seasons, either high or low, can also play an important role in contaminating waterbodies once a dilution or concentration of contaminants may take place. The present study evaluated the water quality of the Tejereba River (Guarujá, Brazil) during the high season (January) and low season (March and May) in 2018. Reduction in water quality was observed in May, a month with low pluviosity and low tourism. The integrated data analysis (PCA) showed a positive correlation between the physicochemical parameters and the month of May, in which they were negatively correlated with pluviosity and the percentage of tourists. Despite the deterioration of water quality in May, no toxicity to Daphnia magna was observed. Our work showed that water quality (physicochemical and microbiological parameters), during the studied months, is more related to raining seasons than to the presence of tourists in Guarujá, Brazil.